Caveolin-3 Microdomain: Arrhythmia Implications for Potassium Inward Rectifier and Cardiac Sodium Channel - Vaidyanathan, Ravi; Reilly, Louise; Eckhardt, Lee L. (Frontiers in Physiology, 2018)
In human cardiac ventricular myocytes, caveolin-3 functions as a scaffolding and regulatory protein for signaling molecules and compartmentalizes ion channels. Our lab has recently explored this sub-cellular microdomain and found that potassium inward rectifier Kir2.x is found in association with caveolin-3. The three cardiac Kir2.x isoforms (Kir2.1, Kir2.2, and Kir2.3) are the molecular correlate of IK1 in the heart, of which Kir2.1 is the dominant isoform in the ventricle. Kir2.1 channels assemble with Kir2.2 and Kir2.3 forming hetero-tetramers that modulate IK1. IK1 sets the resting membrane potential and assists with terminal phase 3 ventricular repolarization. In our studies using native human ventricular tissue, Kir2.x co-localizes with caveolin-3 and significance of the association between Kir2.x and caveolin-3 is emphasized in relation to mutations in the gene which encodes caveolin-3, CAV3, associated with Long QT Syndrome 9(LQT9). LQT9-associated CAV3 mutations cause decreased current density in Kir2.1 and Kir2.2 as homomeric and heteromeric channels, which affects repolarization and membrane potential stability. A portion of Kir2.1 cardiac localization parallel that of the cardiac sodium channel (Nav1.5). This may have implications for Long QT9 in which CAV3 mutations cause an increase in the late current of Nav1.5 (INa-L) via nNOS mediated nitrosylation of Nav1.5. In iPS-CMs, expression of LQT9 CAV3 mutations resulted in action potential duration (APD) prolongation and early-after depolarizations (EADs), supporting the arrhythmogenicity of LQT9. To evaluate the combined effect of the CAV3 mutants on INa-L and IK1, we studied both ventricular and Purkinje myocyte mathematical modeling. Interestingly, mathematical ventricular myocytes, similar to iPS-CMs, demonstrated EADs but no sustained arrhythmia. In contrast, Purkinje modeling demonstrated delayed-after depolarizations (DADs) driven mechanism for sustained arrhythmia, dependent on the combined loss of IK1 and gain of INa-L. This finding changes the overall assumed arrhythmia phenotype for LQT9. In future studies, we are exploring caveolar micro-domain disruption in heart failure and how this effects Kir2.x and NaV1.5. Here we review the caveolae cardiac microdomain of Kir2.x and Nav1.5 and explore some of the downstream effects of caveolin-3 and caveolae disruption in specific clinical scenarios.